Phylodynamics of major CRF01_AE epidemic clusters circulating in mainland of China - Xiaolin Wang (Nature Portfolio, 2017)
Abstract As the most dominant HIV-1 strain in China, CRF01_AE needs to have its evolutionary and demographic history documented. In this study, we provide phylogenetic analysis of all CRF01_AE pol sequences identified in mainland China. CRF01_AE sequences were collected from the Los Alamos HIV Sequence Database and the local Chinese provincial centers of disease control and prevention. Phylogenetic trees were constructed to identify major epidemic clusters. Bayesian coalescent-based method was used to reconstruct the time scale and demographic history. There were 2965 CRF01_AE sequences from 24 Chinese provinces that were collected, and 5 major epidemic clusters containing 85% of the total CRF01_AE sequences were identified. Every cluster contains sequences from more than 10 provinces with 1 or 2 dominant transmission routes. One cluster arose in the 1990s and 4 clusters arose in the 2000s. Cluster I is in the decline stage, while the other clusters are in the stable stage. Obvious lineage can be observed among sequences from the same transmission route but not the same area. Two large clusters in high-level prevalence were found in MSM (Men who have sex with men), which highlighted that more emphasis should be placed on MSM for HIV control in mainland China.